Undergraduate students’ modular experiences in learning mathematics in the new normal education - Rovinson Deladia Gaganao; Rey Naranja Discar (International Journal of Evaluation and Research in Education (IJERE), 2023)
The modular approach has been proven to be an effective tool in mathematics learning. However, this approach presents challenges regarding students’ learning. Hence, this study was conducted to determine and compare the modular experiences of 55 Bachelor of Secondary Education (BSED) Math students of Eastern Samar State University (ESSU) Salcedo based on gender, age, and year level. The study utilized a descriptive-comparative design and a survey questionnaire. Percentage, mean, t-test, and analysis of variance (ANOVA) were used to treat the data. The study revealed that respondents were satisfied with their modular experience in learning mathematics in the new normal education. Specifically, the respondents rated their experience satisfactory in good teaching, high in clear outcomes, manageable in appropriate workload, moderate in appropriate assessment, and average in generic skills. Furthermore, the study found a significant difference in good teaching, clear outcomes, appropriate workload, appropriate assessment, generic skills, and satisfaction with modular learning across the respondents’ year level, but insignificant across age and gender. Based on the findings, it is recommended that teachers should attend intensive seminars and training on current trends in math teaching and module development. Modules’ quality must be improved considering the workload, assessment, outcomes, and skills development.